Adhesion, friction and tribochemical reactions at the diamond–silica interface. (25th January 2023) - Cutini, Michele; Forghieri, Gaia; Ferrario, Mauro; Righi, Maria Clelia
Abstract: Diamond-based coatings are employed in several technological applications, for their outstanding mechanical properties, biocompatibility, and chemical stability. Of significant relevance is the interface with silicon oxide, where phenomena of adhesion, friction, and wear can affect drastically the performance of the coating. Here we monitor such phenomena in real-time by performing massive ab initio molecular dynamics simulations in tribological conditions. We take into account many relevant factors that can play a role, i.e. the diamond surface orientation and reconstruction, silanol density, as well as, the type and concentration of passivating species. The large systems size and the long simulations time, put our work at the frontier of what can be currently done with fully ab initio molecular dynamics. The results of our work point to hydrogenation as an effective way to reduce both friction and wear for all diamond surfaces, while graphitization is competitive only on the (111) surface. Overall we expect that our observations will be useful to improve technological applications where the silica–diamond interface plays a key role. Moreover, we demonstrate that realistic and accurate in silico experiments are feasible nowadays exploiting HPC resources and HPC-optimized software, paving the way to a more general understanding of the relationship between surface chemistry and nanoscale-tribology.